2006
DOI: 10.1016/j.neuron.2006.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Selective Engagement of Plasticity Mechanisms for Motor Memory Storage

Abstract: The number and diversity of plasticity mechanisms in the brain raises a central question: does a neural circuit store all memories by stereotyped application of the available plasticity mechanisms, or can subsets of these mechanisms be selectively engaged for specific memories? The uniform architecture of the cerebellum has inspired the idea that plasticity mechanisms like cerebellar long-term depression (LTD) contribute universally to memory storage. To test this idea, we investigated a set of closely related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
137
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 81 publications
20
137
0
Order By: Relevance
“…Our data have shown that TRPC3 is required for the induction of cerebellar LTD, which has long been considered as the molecular basis of motor coordination and cerebellar motor learning (Aiba et al, 1994;Kim and Thompson, 1997;De Zeeuw et al, 1998;Feil et al, 2003;Boyden et al, 2006;Hansel et al, 2006). Specifically in TRPC3 knock-out mice, the walking behavior and sEPSC induced through the brief burst of a PF stimulus are impaired (Hartmann et al, 2008).…”
Section: Discussionmentioning
confidence: 75%
“…Our data have shown that TRPC3 is required for the induction of cerebellar LTD, which has long been considered as the molecular basis of motor coordination and cerebellar motor learning (Aiba et al, 1994;Kim and Thompson, 1997;De Zeeuw et al, 1998;Feil et al, 2003;Boyden et al, 2006;Hansel et al, 2006). Specifically in TRPC3 knock-out mice, the walking behavior and sEPSC induced through the brief burst of a PF stimulus are impaired (Hartmann et al, 2008).…”
Section: Discussionmentioning
confidence: 75%
“…Long-term associative plasticity in the flocculus in vitro: Temporal requirements matched to behavioral function Our finding that coincident parallel fiber and climbing fiber stimulation failed to induce LTD in the flocculus was surprising, given the multiple lines of evidence for a role of climbing fiber-triggered LTD in flocculus-dependent learning (e.g., Boyden et al, 2006;Hansel et al, 2006;Ito, 2001;Kimpo et al, 2014;Medina and Lisberger, 2008). However, in vivo, the activation of climbing fibers by performance errors would be delayed relative to the parallel fiber activity that caused the error, rather than coincident.…”
Section: Heterogeneity In the Rules For Long-term Plasticity At Cerebmentioning
confidence: 99%
“…For the VOR adaptation the conditioning stimuli consisted of turntable and drum sinusoidal oscillations on the vertical axis in the light (Boyden et al 2006;Kimpo et al 2005). Two different sets of oscillation parameters were used to induce VOR decrease (gain-down conditioning) and increase (gain-up conditioning), respectively (Fig.…”
Section: Equipment Stimuli and Drug Administrationmentioning
confidence: 99%